Training Models in Professional Psychology Education (A Literature Review) - Anrilia E. M. Ningdyah; Edward Helmes; Claire Thompson; Garry Kidd; Kenneth Mark Greenwood (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2016)
Intense debate on training models used in professional psychology education, including discussion on the specific training models most appropriate for educating future psychologists is far from finished. The authors reviewed articles discussing training models including results of empirical studies in professional psychology programs, which were published in several psychology journals databases (1949 to 2014). The authors have identified (a) the scientist-practitioner; (b) the practitioner model and its derivatives; (c) the clinical-scientist; and (d) the competency-based models. This article also outlines the historical development of each model and a consideration of the main principles espoused by each training model. It seems that discussion on the concept of training models and empirical studies on how these models are used in professional psychology programs outside the context of Western countries, is rare. Thus, this review could serve as a theoretical foundation for the implementation of a study aimed at filling the gap in the discussion of professional psychology program curricula, including the training models used, especially in other contexts than the Western.